Effect of Diet Dilution in the Starter Period on Performance and Carcass Characteristics of Broiler Chicks - Teimouri, A.; Rezaei, M.; Pourreza, J.; Sayyahzadeh, H.; Waldroup, P.W. (International Journal of Poultry Science, 2005)
The effect of energy and protein dilution in the starter period (8 to 14 days) of age, on performance and carcass characteristics of 360 Arian male chicks was studied in a completely randomized design. This experiment consisted of 6 treatments, 4 replicates, with 15 chicks per replicate. In order to dilute the diets six levels (0, 4, 8, 12, 16, and 20) percent of ground wood charcoal was used. Chicks were fed with starter and grower diet from 15 to 21 and 22 to 42 days of age respectively. During the experiment feed intake, body weight gain, feed conversion ratio were measured weekly. Mortality was measured throughout the experiment. At 43 day of age 4 chicks each treatment was selected and carcass characteristics were measured. The results indicated that dilution of diet from 8 to 14 days of age increased feed intake in this period but, the differences were not significant. With increasing dilution rate body weight gain of chicks significantly decreased in comparison to control group (P< 0.05). Due to compensatory growth after restricted period, there was not significant difference in body weight among restricted and control groups at 42 days of age. There was not significant difference among the treatments for feed conversion ratio in whole period of the experiment (8 to 42 day). Similarly, there was not significant difference among the treatments for caloric conversion ratio in whole period of the experiment (8 to 42 day). Mortality rate in restricted groups was significantly lower than control group (P< 0.05). Diet dilution hadn`t significant effect on carcass, breast meat, drumsticks, thighs, liver, intestine, abdominal fat percentages. The results of the present study indicated that broiler chicks can withstand a 7-day period (from 8 to 14 days) feed restriction with ground wood charcoal in early age without loss in performance.